Learner Development in Education for the Future - Žadeikaitė, Loreta; Petruškevičiūtė, Auksė (Pedagogika, 2013)
Doctor Meilė Lukšienė, pioneer of education reform and founder of the national school, recognized the changes in the educational curriculum to be the main area of reform in the Lithuanian education system and gave her insights about the concept of education and the changes in the educational curriculum. This article analyses the way M. Lukšienė’s ideas are reflected in the Lithuanian education system, including the influence her ideas had on the changes in the educational curriculum on both theoretical/legislative and practical levels. The article provides a review of the evolution of the curriculum concept based on M. Lukšienė’s ideas. Productive learning, an example relating to constructing the curriculum process of alternative education, is presented; it combines learning at school which must be responsive to individual needs, with learning in real life, i.e. sites of practical training (production sites, organizations, offices). This form of education is being implemented within the Alternative Education project in three Lithuanian schools. Productive learning is presented as a novelty in the education system. The evaluation made by both teachers and students of the changes that occurred within the first year of implementing productive learning is presented in the article. Methods of research applied: descriptive analysis of scientific literature and legal documents, including creative content analysis. The results of research revealed that productive learning helps students overcome their fear of school, improves student achievement and attendance, generates new possibilities for students to discover their hidden talents and express them, creates conditions for students to form a healthy relationship with their environment, and enables teachers to enjoy success in their pedagogical efforts. This educational innovation requires further reinforcement at all levels, including the strengthening of school communities by creating a unique curriculum process and scientific research to make these innovations available to other educational establishments.